Measurement of radioactivity in building materials – Problems encountered caused by possible disequilibrium in natural decay series. (20th April 2018) - Michalik, Boguslaw; de With, Govert; Schroeyers, Wouter
Highlights: Disequilibrium situations in uranium and thorium decay series are discussed. Assumption necessary to analyze gamma spectra of natural radionuclides are listed. Possible variations of activity index are showed. Related uncertainty in exposure assessment are underlined. Abstract: The determination of the activity concentration of naturally occurring radionuclides in construction materials is based on the principles of gamma-spectrometry. Gamma spectrometry is a comparative method and therefore includes many parameters that are specific to the test sample and measurement circumstances. Consequently, several of the testing conditions must be verified prior to testing and/or require correction to obtain accurate results. Besides problems encountered during the measurement, the interpretation of the results and calculation of the activity indices, needed for material classification, may lead to significant mistakes. Current regulation in the European Union requires to calculate an activity concentration index (index I) using the activity concentration of 226 Ra, 232 Th and 40 K. Not all of these radionuclides are directly measurable by gamma spectrometry and, to determine the index, additional assumptions have to be made about secular equilibrium in uranium and thorium decay series. These assumptions are often not valid in case of NORM (Naturally Occurring Radioactive Materials) where long term lack of secular equilibrium in the uranium and/or thorium decay series is often observed. As a consequence, this may result in an underestimation or overestimation of the index. The article discusses specific disequilibrium situations in building materials. Sources for potential inaccurate determinations and misinterpretation are identified and practical mitigation options are proposed.